Analysis of Non-Performing Loans Based on Internal and External Factors at The Karya Sentosa Market Traders Cooperative in Batu City - Yufilda Maya Sira; Ida Iriani, Nur; Mukoffi, Ahmad (International Journal of Management and Business, 2025)
Cooperatives are economic organizations owned and run by their members to achieve common economic goals. Internal and external variables can cause bad debts. This research analyzes the Non-Performing Loans Based on Internal and External Factors at The Karya Sentosa Market Traders Cooperative in Batu City (Koperasi Pedagang Pasar Karya Sentosa Kota Batu). A qualitative descriptive research approach was used. This study's data collection methods were literature review, interviews, and observations. This research finds that internal factors that cause bad debt include a weak credit analysis system and a lack of credit supervision. Otherwise, external factors causing bad debt include debtors' financial factors, intentional factors, and debtor character. Several strategies for handling bad debts consist of taking advantage of external opportunities, increasing internal strength by strengthening cooperative teamwork, increasing internal strength by increasing the number of collectors, and increasing the capacity of human resources in credit management. Furthermore, it is better to add members to collect to make the installment collection process easier in credit supervision.